Non-classical congenital adrenal hyperplasia presenting as primary amenorrhoea with virilization - CS, Beeresh; Doopadapalli, Divyasree; Ray, Amita; Lingegowda, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary amenorrhea presents a diagnostic challenge even to the most experienced clinicians. The number, variety and the complexity of disorder that must be considered can seem daunting and in many instances include unfamiliar organ system. One such disorder is congenital adrenal hyperplasia (CAH). Here, we present a case of Non-classical congenital adrenal hyperplasia in a 16 year old female who presented to us with primary amenorrhea with virilization. This is an interesting case because of its unusual presentation, difficulty in diagnosis and complexity involved in treatment.